Evidence for the existence of facilitatory interactions between the dopamine D2 receptor and the oxytocin receptor in the amygdala of the rat. Relevance for anxiolytic actions - Hernández-Mondragón, Juan Carlos; Hernández-Hernández, Dexter A.; Crespo-Ramírez, Minerva; Prospero-García, Oscar; Rocha-Arrieta, Luisa; Fuxe, Kjell; Borroto-Escuela, Dasiel O.; Perez de la Mora, Miguel (Frontiers in Pharmacology, 2023)
The amygdala is a limbic region of high value for understanding anxiety and its treatment. Dopamine D2R (D2R) and oxytocin receptors (OXTR) have both been shown to participate in modulating anxiety involving effects in the amygdala. The goal is to understand if D2R-OXTR heterocomplexes exist in Amygdaloid D2R and OXTR interactions 2 the central amygdala and, through enhancing allosteric receptor-receptor interactions, may enhance anxiolytic actions. The methods used involve the shock-probe burying test, the in-situ proximity ligation assay, image acquisition and analysis, and the BRET2 assay. Bilateral cannulas were introduced into the amygdala, and the effects of the co-administration of oxytocin and the D2R-like agonist quinpirole into the amygdala were studied. The combined treatment enhanced the anxiolytic effects versus the single treatment. The D2R/D3R antagonist raclopride blocked the effects of the combined treatment of oxytocin and the D2R agonist although oxytocin is regarded as a distinct modulator of fear mediating anxiolytic effects. In situ proximity ligation assay results indicate the existence of D2R-OXTR heteroreceptor complexes and/or the co-location of OXTR and D2R within the same cell membrane nanodomains in the central amygdala. With BRET2, evidence is given for the existence of D2R-OXTR heteromers in HEK293 cells upon co-transfection. The enhanced behavioral effects observed upon cotreatment with OXTR and D2R agonists may reflect the existence of improved positive receptor-receptor interactions in the putative D2R-OXTR hetero complexes in certain neuronal populations of the basolateral and central amygdala. The D2R-OXTR heterocomplex, especially upon agonist coactivation in the central amygdala, may open a new pharmacological venue for the treatment of anxiety.